An experimental investigation into some of the problems associated with stress diffusion in the vicinity of chord-wise cut-outs in the wing, and a comparison with existing theories - Brown, L. W. (College of Aeronautics, Cranfield, 1954)
Chord-wise openings in the skin between the spars of the wing are designed in some aircraft for undercarriage doors, bomb bay doors, and the wing fold joints of naval Aircraft. Stress concentrations exist in the region of these cut-outs where the load is transferred from the stringers and skin into the concentrated load carrying members. Two theories have evolved to predict the resulting behaviour of the structure. The stringer sheet' theory predicts an infinite shear stress in the corners of the sheet; the 'finite stringer' theory predicts a high, finite shear stress in the corners, the magnitude of which increases with the number of stringers.